Eco-friendly nutrient management practices for increasing cropping cycle in shifting cultivation - L K BAISHYA; NINGSHIYANGERLA WALLING; TEMJENNA JAMIR; S K RAY; MANOJ KUMAR; CHRISTY SANGMA; D J RAJKHOWA (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted in shifting cultivated lands of Nagaland (Wokha and Longleng) during pre-kharif season of 2017 and 2018. Experimental results revealed that combined application of organic manure with bio-fertilizer and micro-dosing of NPK in maize (Zea mays L.) and upland rice (Oryza sativa L.) were the most productive and sustainable eco-friendly nutrient management practices evident by per cent increase in yield by 71.8% and 250%, respectively, over control (jhum practices). However, lime with bio-fertilizer and micro-dosing of NPK application in soybean [Glycine max (L.) Merr.] and groundnut (Arachis hypogaea L.) found productive and sustainable yield with 106% and 62.3% increase, respectively, over control (jhum practices). The maximum values of gross and net returns, crop profitability and production efficiency were computed with organic manure with bio-fertilizer and micro-dosing of NPK for all four crops which were closely followed by lime with bio-fertilizer and micro-dosing of NPK. The energy use efficiency was highest for groundnut (177.70%) followed by upland rice (144.28%), soybean (137.47%) and maize (14.20%). Considerable amount of soil organic carbon (1.1–1.2%), available nitrogen (92.50–185.50 kg N/ha), phosphorus (13.89–17.36 kg P/ha) and potassium (500.60–733.00 kg K/ha) were also retained with eco-friendly nutrient management practices after 2nd year jhum with a potential to continue cropping for another year in the same plot.